2010
DOI: 10.1093/nar/gkq127
|View full text |Cite
|
Sign up to set email alerts
|

Trinucleotide repeats in human genome and exome

Abstract: Trinucleotide repeats (TNRs) are of interest in genetics because they are used as markers for tracing genotype–phenotype relations and because they are directly involved in numerous human genetic diseases. In this study, we searched the human genome reference sequence and annotated exons (exome) for the presence of uninterrupted triplet repeat tracts composed of six or more repeated units. A list of 32 448 TNRs and 878 TNR-containing genes was generated and is provided herein. We found that some triplet repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
149
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(157 citation statements)
references
References 79 publications
8
149
0
Order By: Relevance
“…Finally, how do the various triplet repeats differ in their susceptibility to cellular ribonucleases? A survey of triplet repeats, which are present in about 4% of human mRNAs, revealed that some of these repeats are highly prevalent, whereas others are either rare or absent (61). CNG repeats, associated with human neurological diseases, are among the most frequent repeat types and have attracted the highest interest to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, how do the various triplet repeats differ in their susceptibility to cellular ribonucleases? A survey of triplet repeats, which are present in about 4% of human mRNAs, revealed that some of these repeats are highly prevalent, whereas others are either rare or absent (61). CNG repeats, associated with human neurological diseases, are among the most frequent repeat types and have attracted the highest interest to date.…”
Section: Discussionmentioning
confidence: 99%
“…These five repeated motifs constitute 77% of the 1,030 total repeat tracts composed of six or more uninterrupted repeats found in 878 human mRNAs. At the other end of the frequency scale are the CGU, CUA, UAG, CAU, CUU, CGA, and UGG repeats (61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 30 Drosophila proteins possess polyQ tracts of 20 residues or longer, which are conserved in other drosophilid species. In the human proteome, there are several prevalent homo-amino acid tracts, whereby polyQ tracts are the most frequent homo-amino acid tracts encoded by repeats of a single codon (CAG) (Kozlowski et al , 2010 ). Screening of the Saccharomyces cerevisiae protein database ( www.yeastgenome.org ) revealed that polyQ tracts are the most common homopolymeric amino acid tracts of eight amino acids length or longer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they should be reconsidered in the future genetic association. 16,76 PRESENT Single nucleotide polymorphisms The completion of the Human Genome Project is a major scientific development in human genomics and biomedical sciences. The reference DNA sequence has provided the basis for studying genetic variations in the human genome among individuals in populations.…”
Section: Tandem Repeatsmentioning
confidence: 99%